Energy metabolism and the intestinal barrier: implications for understanding and managing intestinal diseases - Chen, Shuai; Shen, Caifei; Zeng, Xiaorui; Sun, Luqiang; Luo, Fangli; Wan, Renhong; Zhang, Yupeng; Chen, Xinyun; Hou, Yujun; Wang, Wen; Zheng, Qianhua; Li, Ying (Frontiers in Microbiology, 2025)
The interplay between energy metabolism and the gut barrier is crucial for maintaining intestinal physiological homeostasis. Energy metabolism and the intestinal barrier perform distinct yet complementary roles that uphold intestinal ecological equilibrium. Disruptions in energy metabolism can compromise the integrity of the intestinal barrier; for example, inactivation of the AMPK pathway may lead to reduced expression of proteins associated with tight junctions. Conversely, impairment of the intestinal barrier can result in metabolic dysregulation, such as alterations in the gut microbiota that impede the production of short-chain fatty acids (SCFAs), which are essential substrates for energy metabolism. This disruption can affect energy production and modify the gut’s hypoxic environment. Imbalances in these systems have been associated with the onset of various intestinal diseases. Research indicates that dietary interventions, such as a low FODMAP diet, can enhance the colonization of probiotics and improve the fermentation metabolism of SCFAs. Pharmacological strategies to elevate SCFA levels can activate the AMPK pathway and rectify abnormalities in energy metabolism. This review provides a comprehensive summary of recent advancements in elucidating the interactions between energy metabolism and the intestinal barrier.